2007
DOI: 10.1111/j.1468-3083.2007.02297.x
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed dye laser: what's new in non‐vascular lesions?

Abstract: With PDL, it is possible to achieve good results with numerous, partly less well-known indications (i.e. lupus erythematosus). With other diseases, PDL has so far been considered to be a complementary therapy method or to be in an experimental state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
49
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 89 publications
(123 reference statements)
0
49
0
2
Order By: Relevance
“…23,24 Several studies have reported the improvement of the clinical appearance of striae with 585-nm pulsed dye laser (PDL) via enhancement of the extracellular matrix collagen. [25][26][27][28] In addition, it has a modest efficacy in decreasing the erythema of striae rubra; however, it has [29][30][31][32] More recently, there has been evidence that indicates the benefits of both fractionated non-ablative and ablative lasers in increasing collagen fibers, and improving the appearance of striae alba. Our study aimed to assess the effectiveness a fractionated CO 2 in the treatment of striae alba, especially in darker skin types.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 Several studies have reported the improvement of the clinical appearance of striae with 585-nm pulsed dye laser (PDL) via enhancement of the extracellular matrix collagen. [25][26][27][28] In addition, it has a modest efficacy in decreasing the erythema of striae rubra; however, it has [29][30][31][32] More recently, there has been evidence that indicates the benefits of both fractionated non-ablative and ablative lasers in increasing collagen fibers, and improving the appearance of striae alba. Our study aimed to assess the effectiveness a fractionated CO 2 in the treatment of striae alba, especially in darker skin types.…”
Section: Introductionmentioning
confidence: 99%
“…Bulafl›c› olmas› nedeniyle toplumda ve özellikle pediatrik-adult döneminde görülme s›kl›¤› %10 civar›ndad›r 2,3 . HPV, DNA virüsüdür ve HPV'nin 100'den fazla genotipi tespit edilmifltir 4,5 .…”
Section: Giriflunclassified
“…Dermatological lesions that represent the target may be considered typical vascular lesions, vascular dependent lesions, or nonvascular lesions, according to a recent classification [1]. …”
Section: Introductionmentioning
confidence: 99%
“…Nonvascular lesions, on the other hand, include viral infections like molluscum contagiosum as well as other cutaneous conditions, for example, xanthelasma palpebrarum [113]. …”
Section: Introductionmentioning
confidence: 99%